2015
DOI: 10.1175/jpo-d-14-0042.1
|View full text |Cite
|
Sign up to set email alerts
|

Interannual Variability of the Mixed Layer Winter Convection and Spice Injection in the Eastern Subtropical North Atlantic

Abstract: International audienceThe Argo dataset is used to study the winter upper-ocean conditions in the northeastern subtropical (NEA) Atlantic during 2006–12. During late winter 2010, the mixed layer depth is abnormally shallow and a negative anomaly of density-compensated salinity, the so-called spiciness, is generated in the permanent pycnocline. This is primarily explained by unusual weak air–sea buoyancy flux during the late winter 2010, in contrast with the five other studied winters. Particularly deep mixed la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 107 publications
0
13
0
Order By: Relevance
“…Qiu and Huang (1995) pointed out that the annual excursion of the mixed layer depth greatly exceeds the vertical Ekman pumping. As a result, the subduction rates are governed primarily by the rapid shoaling of the mixed-layer depth in response to surface buoyancy gain (Kolodziejczyk et al, 2015;Liu & Huang, 2011;Trossman et al, 2009). Qu et al (2016) provided additional evidence for the sensitivity of STUW to the mixed layer change: STUW is produced at the intersection of the mixed layer front (or the mixed layer sharp transition zone) and the outcrop isohalines.…”
Section: 1002/2017gl075772mentioning
confidence: 99%
“…Qiu and Huang (1995) pointed out that the annual excursion of the mixed layer depth greatly exceeds the vertical Ekman pumping. As a result, the subduction rates are governed primarily by the rapid shoaling of the mixed-layer depth in response to surface buoyancy gain (Kolodziejczyk et al, 2015;Liu & Huang, 2011;Trossman et al, 2009). Qu et al (2016) provided additional evidence for the sensitivity of STUW to the mixed layer change: STUW is produced at the intersection of the mixed layer front (or the mixed layer sharp transition zone) and the outcrop isohalines.…”
Section: 1002/2017gl075772mentioning
confidence: 99%
“…For instance, AW is a warm and salty water mass compared to cold and fresh polar waters of same density. From a general perspective, spicy waters are formed in the subtropics by the strong evaporation and vertical mixing (Kolodziejczyk et al, ; Yeager & Large, ) before flowing poleward along with western boundary currents (Laurian et al, ). At higher latitudes, those waters play an important role in air‐sea interactions and oceanic heat transport (Kwon et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…There was weak correlation between temperature and salinity variability in this region and during this season. Kolodziejczyk et al (2014b) indicated that summer 2012 conditions in the salinity maximum were influenced by anomalously salty subsurface waters that originated farther to the northeast at the end of the previous winter and by locally salty surface waters.…”
Section: Introductionmentioning
confidence: 99%